Relasi Manusia dan Teknologi Digital dalam Perspektif Filsafat Yin dan Yang: Human Relations and Digital Technology in the Perspective of Yin and Yang Philosophy - Trianto, Syaifullah Aji; Priatmojo, Dhewangga (Jurnal Filsafat Indonesia, 2025)
The relationship between humans and digital technology has raised concerns about its impact on real human life, where human identity and existence are often submerged in virtual reality. This article aims to explore and rebuild the ideal relationship between humans and digital technology through the perspective of Yin and Yang philosophy. This research uses a qualitative method with a literature analysis approach to understand the principles of Yin and Yang and their relevance in the context of digital technology. The results show that the principles of distinction, relativity, and dynamics promoted by Yin and Yang philosophy can be applied to improve human relationships with digital technology. By utilizing these principles, humans can find a harmonious balance between life in the real world and interaction with the digital world, so that technology again functions as a tool that enriches human life without sacrificing their existence and well-being in the real world.